Design of an Electronic Load Controller for Micro Hydro Power Plant Using Fuzzy-PI Controller. Issue 1 (31st December 2022) - Ofosu, Robert Agyare; Normanyo, E.; Kaberere, K. K.; Kamau, S. I.; Otu, E. K.
Abstract: This paper presents the design of an ELC to control the frequency of the MHPP for a purely resistive unbalanced 3-phase load. This is necessary since most of the researches done on ELC in MHPPs considered the design using balanced 3-phase load. However, in real world the 3-phase load at each phase varies due to the different consumers connected to each phase. In this work, a fuzzy-PI controller was designed to reduce the steady state error of the frequency variations and also optimize the gains of the conventional PI controller. These gains were then used to generate equivalent Pulse Width Modulation (PWM) signals to control the firing of Insulated Gate Bipolar Transistors (IGBTs) to dump excess power to the damper loads when the consumer loads change to maintain the power at the generator output constant. Simulation results of the MHPP under varying unbalanced loads showed that the designed ELC was efficient in maintaining the frequency of the MHPP at 50 Hz with a tolerance of ±2. The ELC also maintained the output power of the generator by ensuring the balance of power between the consumer and damper loads.